2021
DOI: 10.3389/fpsyt.2021.672347
|View full text |Cite
|
Sign up to set email alerts
|

Current Advances in Wearable Devices and Their Sensors in Patients With Depression

Abstract: In this study, a literature survey was conducted of research into the development and use of wearable devices and sensors in patients with depression. We collected 18 studies that had investigated wearable devices for assessment, monitoring, or prediction of depression. In this report, we examine the sensors of the various types of wearable devices (e.g., actigraphy units, wristbands, fitness trackers, and smartwatches) and parameters measured through sensors in people with depression. In addition, we discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 53 publications
2
40
0
Order By: Relevance
“…This study will only recruit Japanese subjects; whether the same diagnostic accuracy can be achieved in other ethnic groups is unclear. In addition, although the information obtained by Silmee is similar to that of wearable devices used in other studies, 15 the accuracy and content of the information obtained may change in the future as the performances of wearable devices improve. In the future, it would be desirable to mount the system on other wearable devices.…”
Section: Discussionmentioning
confidence: 60%
“…This study will only recruit Japanese subjects; whether the same diagnostic accuracy can be achieved in other ethnic groups is unclear. In addition, although the information obtained by Silmee is similar to that of wearable devices used in other studies, 15 the accuracy and content of the information obtained may change in the future as the performances of wearable devices improve. In the future, it would be desirable to mount the system on other wearable devices.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, qualitative studies should be carried out to investigate the specific causes of dropout. Regarding the use of ICTs, more studies are needed to determine how to improve adherence and compliance rates so that people can wear wearable devices continuously for 24 h ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, wearable devices have been proven to be feasible and acceptable for use among overweight people with severe mental illness ( 19 ). These devices allow for monitoring behaviors in real-time in an unobtrusive way, enabling people to monitor and change their own activity ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with our study in terms of variability but are contrary to in terms of average. Therefore, in future studies, it is necessary to closely examine the associations between the objective and subjective aspects of the sleep quality and the level of depression Wearable devices yield objective sleep measurements via real-time recording at minimal expense, and do not burden users (12); such devices facilitate the personalized and interactive healthcare (50). In this study, we used Fitbit Charge 2 as the wearable device and a previous study showed that sleep parameters measured with Fitbit devices were not statistically different from those measured with actigraphy (51); actigraphy has been used in chronobiology and sleep medicine for the past 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Wearable devices yield objective sleep measurements via real-time recording at minimal expense, and do not burden users ( 12 ); such devices facilitate the personalized and interactive healthcare ( 50 ). In this study, we used Fitbit Charge 2 as the wearable device and a previous study showed that sleep parameters measured with Fitbit devices were not statistically different from those measured with actigraphy ( 51 ); actigraphy has been used in chronobiology and sleep medicine for the past 20 years.…”
Section: Discussionmentioning
confidence: 99%